A systematic map and in-depth review of European telehealth interventions efficacy for chronic obstructive pulmonary disease. (October 2019) - Gaveikaite, Violeta; Grundstrom, Casandra; Winter, Stefan; Chouvarda, Ioanna; Maglaveras, Nicos; Priori, Rita
Abstract: Background: Evidence to support the implementation of telehealth (TH) interventions in the management of chronic obstructive pulmonary disease (COPD) varies throughout Europe. Despite more than ten years of TH research in COPD management, it is still not possible to define which TH interventions are beneficial to which patient group. Therefore, informing policymakers on TH implementation is complicated. We aimed to examine the provision and efficacy of TH for COPD management to guide future decision-making. Methods: A mapping study of twelve systematic reviews of TH interventions for COPD management was conducted. This was followed by an in-depth review of fourteen clinical trials performed in Europe extracted from the systematic reviews. Efficacy outcomes for COPD management were synthesized. Results: The mapping study revealed that systematic reviews with a meta-analysis often report positive clinical outcomes. Despite this, we identified a lack of pragmatic trial design affecting the synthesis of reported outcomes. The in-depth review visualized outcomes for three TH categories, which revealed a plethora of heterogeneous outcomes. Suggestions for reporting within these three outcomes are synthesized as targets for future empirical research reporting. Conclusion: The present study indicates the need for more standardized and updated systematic reviews. Policymakers should advocate for improved TH trial designs, focusing on the entire intervention's adoption process evaluation. One of the policymakers' priorities should be the harmonization of the outcome sets, which would be considered suitable for deciding about subsequent reimbursement. We propose possible outcome sets in three TH categories which could be used for discussion with stakeholders. Highlights: Systematic reviews do not recommend TH services even when showing positive results. To advance the field standardized outcomes sets are proposed for future trials. Our analysis could be used to agree on clinical outcomes facilitating reimbursement. Most RCTs ignore preventative actions for mild and non-stable COPD patients.